Synthesis and Electrochemical Properties of Two-Dimensional RGO/Ti3C2Tx Nanocomposites - Shen, Changjie; Wang, Libo; Zhou, Aiguo; Wang, Bo; Wang, Xiaolong; Lian, Weiwei; Hu, Qianku; Qin, Gang; Liu, Xuqing (Nanomaterials (Basel, Switzerland), 2018)
MXene is a new type of two-dimensional layered material. Herein, a GO/Ti3C2Tx nanocomposite was prepared by a simple liquid phase method, and the obtained GO/Ti3C2Tx was transformed into RGO/Ti3C2Tx under high temperature with Ar/H2. The prepared samples were characterized using X-ray diffraction (XRD), Raman measurement, scanning electron microscopy (SEM), energy disperse spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). As an electrode material in lithium-ion batteries, the RGO/Ti3C2Tx nanocomposite exhibited an excellent electrochemical performance and an excellent rate performance. Compared to pure Ti3C2Tx, the nanocomposite had a better reversible capacity at different current densities and had no attenuation after 200 cycles, which is one time higher than pure Ti3C2Tx. The improvement in the specific capacity was due to the excellent electrical conductivity and the unique structure of RGO, in which a charge transfer bridge was built among the Ti3C2Tx flakes. Such a bridge shortened the transmission distance of the electrons and ions and effectively controlled the restacking of the laminated materials.